Finite Element Analysis of the Limit Load of Straight Pipes with Local Wall-Thinning Defects under Complex Loads - Yan Li; Bingjun Gao; Shuo Liu; Kaiming Lin; Juncai Ding (Applied Sciences, 2022)
Local wall thinning is a common defect on the surface of pipelines, which can cause damage to the pipeline under complex pipeline loads. Based on the study on the limit load of straight pipes with defects, the nonlinear finite element method was used to analyze the limit load of straight pipes with local wall-thinning defects under internal pressure, bending moment, torque, axial force, and their combinations, and the empirical limit-load equations of straight pipes with local wall-thinning defects under single and complex loads were fitted. Based on the allowable load on the equipment nozzles, the influences of torque and axial force on the load-bearing capacity of straight pipes with local wall-thinning defects were quantitatively analyzed. For medium and low-pressure equipment, the load-bearing capacity was reduced by 0.59~1.44% under the influence of torque, and by 0.83~1.80% under the influence of axial force. For high-pressure equipment, the load-bearing capacity was reduced by 10.07~20.90% under the influence of torque, and by 2.01~12.40% under the influence of axial force.